2017
DOI: 10.1101/238071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring Phylogenetic Networks Using PhyloNet

Abstract: Abstract.---PhyloNet was released in 2008 as a software package for representing and analyzing phylogenetic networks. At the time of its release, the main functionalities in PhyloNet consisted of measures for comparing network topologies and a single heuristic for reconciling gene trees with a species tree. Since then, PhyloNet has grown significantly. The software package now includes a wide array of methods for inferring phylogenetic networks from data sets of unlinked loci while accounting for both reticula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
109
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 33 publications
1
109
0
Order By: Relevance
“…Mosquito dataset re-analysis. Our re-analysis of the 18-taxon dataset published by Neafsey et al [46] confirmed the historical introgression in the Anopheles phylogeny that was detected by Fontaine et al [51] and Wen et al [52] by analyzing a smaller 6-taxon was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Empirical Studysupporting
confidence: 82%
See 1 more Smart Citation
“…Mosquito dataset re-analysis. Our re-analysis of the 18-taxon dataset published by Neafsey et al [46] confirmed the historical introgression in the Anopheles phylogeny that was detected by Fontaine et al [51] and Wen et al [52] by analyzing a smaller 6-taxon was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Empirical Studysupporting
confidence: 82%
“…The two-reticulation species phylogeny inferred by FastNet(MPL) is shown in Figure 3, where reticulations are visualized in a manner similar to [13]. (shown as Figure 1C in [51]) and the MLE-inferred species phylogeny reported by Wen et al [52], both of which were inferred using the 6-taxon Fontaine et al…”
Section: Empirical Studymentioning
confidence: 99%
“…Strictly bifurcating trees may not adequately depict evolutionary history when gene flow and hybridization are prevalent (SolĂ­s‐Lemus & AnĂ©, ; Wen, Yu, Zhu, Nakhleh, & Posada, ; Yu & Nakhleh, ). Using SNaQ, we found hybridization within the sampled taxa of the C. triseriatus group to be relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in phylogenomic networks continues to increase as more evidence accumulates suggesting that both incomplete lineage sorting and reticulation/hybridization may be a common component of the evolutionary history of several groups (SolĂ­s‐Lemus & AnĂ©, ; SolĂ­s‐Lemus et al, ; Wen et al, ). Unfortunately, many of these explicit network methods are computationally demanding (Than, Ruths, & Nakhleh, ), necessitating the use of some type of approximation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation